Coronary CT Angiography for Coronary Artery Disease: The Current Status and Future Challenges - Saskia Dyah Handari (Universitas Brawijaya, 2023)
Coronary computed tomographic angiography, often known as CCTA, is quickly becoming the diagnostic technique of choice for determining the existence of coronary artery disease (CAD). In the future, CCTA may play an essential part as a